A bibliometric and emerging trend analysis on stress granules from 2011 to 2020: A systematic review and bibliometrics analysis. Issue 29 (22nd July 2022) - Yu, Haiyang; Chen, Qinhao; Pan, Yueyin
Abstract : Background: Stress granules (SGs) are the dense granules formed in the cytoplasm of eukaryotic cells in response to stress stimuli, such as endoplasmic reticulum stress, heat shock, hypoxia, and arsenate exposure. Although SGs have been attracting a lot of research attention, there is still a lack of systematic analysis of SGs in the literature. Methods: By analyzing the literature published in the Web of Science database using the R software, we extracted all the information related to SGs from the literature and cited references. The following information was included: publications per year, overall citations, top 10 countries, top 10 authors, co-author collaborations, top 10 institutions, critical areas, and top 10 cited research articles. Results: A total of 4052 articles related to SGs were selected and screened. These documents have been cited a total of 110, 553 times, with an H-index of 126 and an average of 27.28 citations per article. The authors of the literature included in this study were from 89 different countries/regions. The United States and China had the highest number of publications and ranking institutions. Conclusions: This article presents essential insights on the characteristics and influence of SGs, demonstrating their indispensable role in immune regulation and other fields.